1963
DOI: 10.1128/jb.86.3.510-516.1963
|View full text |Cite
|
Sign up to set email alerts
|

NEW TYPE OF STREPTOMYCIN RESISTANCE RESULTING FROM ACTION OF THE EPISOMELIKE MUTATOR FACTOR IN ESCHERICHIA COLI

Abstract: New type of streptomycin resistance resulting from action of the episomelike mutator factor in Escherichia coli. J. Bacteriol. 86:510-516. 1963.-Analyses have been performed to elucidate the genetic nature of the streptomycin resistance that results from the action of the previously described episomelike mutator factor in Escherichia coli. This streptomycin resistance has been found to differ from ordinary one-step streptomycin resistance. The new type of streptomycin resistance, "mutator resistance," can be l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1967
1967
1972
1972

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…The normal gene for streptomycin sensitivity is present in the mutator-streptomycin resistant cells (81, a fact that might imply that their ribosomes are unchanged. The possibility of this resistance being due to a suppressor mechanism has formerly been suggested (8). This would result in a quantitative rather than a qualitative change, which is reconcilable with the present experimental data.…”
Section: Table 1 Effect Of Streptomycin On Poly-u-stimulated Synthesisupporting
confidence: 89%
See 3 more Smart Citations
“…The normal gene for streptomycin sensitivity is present in the mutator-streptomycin resistant cells (81, a fact that might imply that their ribosomes are unchanged. The possibility of this resistance being due to a suppressor mechanism has formerly been suggested (8). This would result in a quantitative rather than a qualitative change, which is reconcilable with the present experimental data.…”
Section: Table 1 Effect Of Streptomycin On Poly-u-stimulated Synthesisupporting
confidence: 89%
“…Bacterial strains: K12 T71, T71 str-r, T71Mu, T71Mu str-r and T71Mu thr his str-r have formerly been described (11,8). The bacteria were grown in Heart Infusion Broth (Difco).…”
Section: A T E R I a L S A N D M E T H O D Smentioning
confidence: 99%
See 2 more Smart Citations
“…No unstable mutations or other plasmid-chromosome interactions have been observed that might be due to the effects of "controlling episomes" postulated by Dawson and Smith-Keary (53), nor have specific "mutator" episomes acting on specific chromosomal loci been seen. Two examples of elevated mutation frequency of specific loci thought to represent "mutator episome" effects both involved transmissible R factors (88,94,95) and can be interpreted as the occurrence of mutations whose effects are synergistic to R-linked resistance determinants, and whose occurrence is facilitated by residual growth of the R+ cells in the presence of the drug at a selective concentration (208).…”
Section: Incompatibilitymentioning
confidence: 99%